2021
DOI: 10.1111/age.13043
|View full text |Cite
|
Sign up to set email alerts
|

Concordance rate in cattle and sheep between genotypes differing in Illumina GenCall quality score

Abstract: Summary Proper quality control of data prior to downstream analyses is fundamental to ensure integrity of results; quality control of genomic data is no exception. While many metrics of quality control of genomic data exist, the objective of the present study was to quantify the genotype and allele concordance rate between called single nucleotide polymorphism (SNP) genotypes differing in GenCall (GC) score; the GC score is a confidence measure assigned to each Illumina genotype call. This objective was achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In 2021, Berry et al quantified the rate of genotype and allele matching between single nucleotide polymorphism (SNP) genotypes differing in GenCall (GC) score on 771 cattle and 80 sheep samples. They found that the effect was larger and more consistent in the cattle population with more individuals than in the sheep population.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Berry et al quantified the rate of genotype and allele matching between single nucleotide polymorphism (SNP) genotypes differing in GenCall (GC) score on 771 cattle and 80 sheep samples. They found that the effect was larger and more consistent in the cattle population with more individuals than in the sheep population.…”
Section: Discussionmentioning
confidence: 99%
“…The confidence of the called genotype is calculated as 1 - genotype cluster probability [ 53 ] with 0 meaning highest confidence and 1 worst confidence. We removed genotype calls above a confidence of 0.05 (default = 0.15) since higher quality genotypes improve the concordance rate with sequencing data [ 54 ]. Furthermore, the call rate of a variant had to exceed the threshold of 0.95 and had to pass QC parameters defined in the best practices [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this context, we should consider that different studies have reported variable amounts of genotyping errors in SNP‐chip datasets (Berry et␣al . 2016, 2021; Wu et␣al . 2019) that may impact the results of the subsequent analyses.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we should consider that different studies have reported variable amounts of genotyping errors in SNP-chip datasets (Berry et al 2016(Berry et al , 2021Wu et al 2019) that may impact the results of the subsequent analyses. For example, genotyping errors have been found to decrease the power to detect genuine associations between phenotype and genotype data (Gordon et al 2002;Sun et al 2004).…”
Section: Introductionmentioning
confidence: 99%